Pheochromocytoma presenting with rhabdomyolysis and acute renal failure: a case report. (13th September 2013) - Celik, Huseyin; Celik, Ozlem; Guldiken, Sibel; Inal, Volkan; Puyan, Fulya Oz; Tugrul, Armagan
Abstract: Rhabdomyolysis ranges from an asymptomatic illness with elevated creatine kinase levels to a life-threatening condition associated with extreme elevations in creatine kinase, electrolyte imbalances, acute renal failure, and disseminated intravascular coagulation. The most common causes are crush injury, overexertion, alcohol abuse, certain medicines, and toxic substances. A number of electrolyte abnormalities and endocrinopathies, including hypothyroidism, thyrotoxicosis, diabetic ketoacidosis, nonketotic hyperosmolar state, and hyperaldosteronism, cause rhabdomyolysis. Rhabdomyolysis and acute renal failure are unusual manifestations of pheochromocytoma. There are a few case reports with pheochromocytoma presenting rhabdomyolysis and acute renal failure. Herein, we report a case with pheochromocytoma crisis presenting with rhabdomyolysis and acute renal failure.